Hubungan Peran Kader Posyandu Dengan Peningkatan Jumlah Imunisasi Balita Di Wilayah Kerja Puskesmas Palakka Kabupaten Bone - Rosmiati Rosmiati (Lembaga Layanan Pendidikan Tinggi (LL-DIKTI) Wilayah IX Sulawesi, 2021)
The role of posyandu cadres is an important factor in immunization activities. In the implementation of immunization activities, the role of cadres is needed so that activities can run on a predetermined schedule, namely informing the public about the days and hours of opening of the posyandu so that people can prepare themselves to participate in posyandu activities in the surrounding area. The purpose of this study was to determine the relationship of the role of posyandu cadres with an increase in the number of under-five immunizations in the working area of the Palakka Health Center in Bone Regency. This type of research is a type of quantitative research using descriptive analytic with a Cross Sectional Study approach. Data collected through a questionnaire. The analysis test used the SPSS computer program, namely SPSS 22 to assess the frequency statistical data and the Chi-Square test on the Pearson bivariate variable obtained a sig value of 0.009 smaller than the 5% significance level. Based on these results it can be concluded that the hypothesis is accepted, meaning that there is a significant relationship between the role of posyandu cadres on the increase in immunization for children under five in the working area of Puskesmas Palakka, Bone Regency. The conclusion of the researchers suggests that posyandu cadres can motivate toddlers' mothers to always bring their toddlers to the posyandu to get immunizations and be diligent in making visits to community homes regarding the importance of immunizing babies and toddlers.